Airway Responsiveness to Inhaled Aspirin is Influenced by Airway Hyperresponsiveness in Asthmatic Patients - Kim, Sungsoo (The Korean Association of Internal Medicine, 2010)
BACKGROUND/AIMS: Many patients with aspirin-induced asthma have severe methacholine airway hyperresponsiveness (AHR), suggesting a relationship between aspirin and methacholine in airway response. This study was performed to determine whether methacholine AHR affects the response of asthmatics to inhaled aspirin. METHODS: The clinical records of 207 asthmatic patients who underwent inhalation challenges with both aspirin and methacholine were reviewed retrospectively. An oral aspirin challenge was performed in patients with a negative inhalation response. The bronchial reactivity index (BRindex) was calculated from the percent decrease in lung function divided by the last dose of the stimulus. RESULTS: Forty-one (20.9%) and 14 (7.1%) patients showed a positive response to aspirin following an inhalation and oral challenge, respectively. Only 24.3 and 14.3% of the responders had a history of aspirin intolerance, respectively. The methacholine BRindex was significantly higher in the inhalation responders (1.46 ± 0.02) than in the oral responders (1.36 ± 0.03, p < 0.01) and in non-responders (n = 141, 1.37 ± 0.01, p < 0.001). The aspirin BRindex was significantly correlated with the methacholine BRindex (r = 0.270, p < 0.001). Three of four patients who received the oral challenge, despite a positive inhalation test, showed negative responses to the oral challenge. Two of these patients had severe AHR. CONCLUSIONS: A considerable number of asthmatic patients with no history of aspirin intolerance responded to the inhalation aspirin challenge. The airway response to aspirin was significantly correlated with methacholine-AHR, and a false-positive response to aspirin inhalation test seemed to occur primarily in patients with severe AHR.